Contraceptive preferences and adoption following female genital fistula surgery in Uganda: a mixed-methods study - Alison M. El Ayadi; Hadija Nalubwama; Caitlyn Painter; Othman Kakaire; Suellen Miller; Justus Barageine; Josaphat Byamugisha; Susan Obore; Abner Korn; Cynthia C. Harper (Reproductive Health, 2023)
Abstract Background Female genital fistula, largely caused by prolonged obstructed labour, is treated by surgical repair. Preventing pregnancy for a minimum period post-repair is recommended to ensure adequate healing and optimize post-repair outcomes. Methods We examined contraceptive preferences and use among Ugandan fistula patients (n = 60) in the year following genital fistula surgery using mixed-methods. Sexual activity, contraceptive use and pregnancy status were recorded quarterly for 12 months after surgery. In-depth interviews among purposively selected participants (n = 30) explored intimate relationships, sexual experiences, reproductive intentions, and contraceptive use. Results Median participant age was 28 years and almost half (48%) were married or living with partners. Counselling was provided to 97% of participants on delaying sexual intercourse, but only 59% received counselling on contraception. Sexual activity was reported by 32% after 6 months and 50% after 12 months. Eighty-three percent reported not trying for pregnancy. Among sexually active participants, contraceptive use was low at baseline (36%) but increased to 73% at 12 months. Six (10%) women became pregnant including two within 3 months post-repair. Interview participants who desired children immediately were young, had fewer children, experienced stillbirth at fistula development, and felt pressure from partners. Women adopted contraception to fully recover from fistula surgery and avoid adverse outcomes. Others simply preferred to delay childbearing. Reasons cited for not adopting contraception included misconceptions related to their fertility and to contraceptive methods and insufficient or unclear healthcare provider advice on their preferred methods. Conclusions A high proportion of patients were not counselled by healthcare providers on contraception. Provision of comprehensive patient-centred contraceptive counselling at the time of fistula surgery and beyond is important for patients to optimize healing from fistula and minimize recurrence, as well as to meet their own reproductive preferences.